The Effecting Factors Achievement Class Average of A Class Public Health 2022 generation - Debora Harsono (British (Jurnal Bahasa dan Sastra Inggris), 2023)
This paper presents afact about the result of English Teaching Learning of A class Public Health 2022 generation.It consists and describes some factors that effecting achievement Class Averageof A class Public Health. Because the Class Average states, there are some factors that effecting the achievement result of English Teaching Learning of A class. To attain the credibility of this research, the researcher uses class average normally datafrom the result of Teaching Learning English subject. Finally, through this paper, we can prove that some factors happen and influence the class average of A class Public Health 2022 generation. In short, we have concluded that A class of 2022 generation has achieved the highest point of class average than the others classes.